Pengembangan Studi Islam Perspektif Insider-outsider - Musnur Hery (Intizar, 2016)
Pengembangan dan pengayaan studi Islam layak memperhatikan epistemologi yang diusung oleh perspektif insider-outsider. Epistemologi yang telah berkembang di dunia Islam seperti al-bayan (rasionalisme), al-burhan (empirisme) dan al-irfan (intuisi) harus diperkuat dengan epistemogi yang berkembang dengan kemajuan pengetahuan yang lazim menjadi pisau bedah analisis outsider seperti fenomenologi agama, distansiasi (penjarakan terhadap objek), apropriasi (penepatan objek bagi horizon diri), kritik ideology (kritik atas prasangka dan ilusi agama), variasi imajinatif (permianan imajinasi makna), dekonstruksi (pembongkaran ilusi dan doktrin mapan), dan hermeneutika (metodologi dan filsafat tafsir). Dengan kolaborasi epistemology insider dan outsider maka tensi antara kajian insider dan outside dapat dijembatani. Terkait yang terakhir ini maka gagasan crosscheck inside-outsider, yakni kajian sarjana tentang agama sebuah masyarakat harus diverifikasi oleh anggota masyarakat tersebut layak diapresiasi.The development and enrichment of Islamic studies ought to pay attention much on epistemology promoted by insider-outsider’s perspective. Epistemology that has evolved in the world of Islam as al-bayan (rationalism), al-burhan (empiricism) and al-irfan (intuition) should be reinforced with Epistemology evolving with the advancement of knowledge that commonly becomes scalpel analysis of outsider like phenomenology of religion, distansiasi ( the spacing of the object), appropriation (Placing the object to the its horizon), criticism of ideology (criticism of prejudices and illusions of religion), variations imaginative (the game of imagined meaning), deconstruction (dismantling of illusion and established doctrine), and hermeneutics (methodology and philosophy of interpretation). With the collaboration of epistemology of insider and outsider, so the tension between insider and outsider studies can be bridged. Related to this, the crosscheck idea of inside-outsider, the undergraduate study of religion in a society, should be verified by members of the community should be appreciated.